2019
DOI: 10.1002/macp.201800496
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Dynamics Simulation of Ethylene/Hexene Copolymer Adsorption onto Graphene: New Insight into Thermal Gradient Interaction Chromatography

Abstract: Crystallization‐based fractionation techniques are powerful methods for the analysis of short‐chain branching (SCB) in linear low‐density polyethylene. Recently, thermal gradient interaction chromatography (TGIC) has been developed for SCB determination of semi‐crystalline and amorphous polyolefins. In TGIC, the fractionation mechanism relies on the interaction of polyolefin chains with a graphite surface upon temperature change for a given solvent strength. Using molecular dynamics simulations, both the entha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 63 publications
0
15
0
Order By: Relevance
“…Except for the use of a solvent gradient in HTLC, all of the rest of the techniques use temperature as the main separation knob and share the following experimental steps: The polymer sample is dissolved in a solvent or an isocratic solvent mixture. A fraction of polymer solution is loaded onto a column at high temperature where polymers are still soluble. The polymer solution is fractionated into different components on the substrates based on their CC while the temperature of column is being cooled at a certain rate. Polymer fractions are eluted by raising flow rate and temperature of the column to achieve further separation and detection. The properties of the eluate are measured by a detector or array of detectors, such as DRI, IR, ,, ELSD, or turbidity, to provide a measure of concentration as a function of temperature. The use of multiple detectors provides additional information.…”
Section: Distribution and Content Of Comonomers In Polyolefinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Except for the use of a solvent gradient in HTLC, all of the rest of the techniques use temperature as the main separation knob and share the following experimental steps: The polymer sample is dissolved in a solvent or an isocratic solvent mixture. A fraction of polymer solution is loaded onto a column at high temperature where polymers are still soluble. The polymer solution is fractionated into different components on the substrates based on their CC while the temperature of column is being cooled at a certain rate. Polymer fractions are eluted by raising flow rate and temperature of the column to achieve further separation and detection. The properties of the eluate are measured by a detector or array of detectors, such as DRI, IR, ,, ELSD, or turbidity, to provide a measure of concentration as a function of temperature. The use of multiple detectors provides additional information.…”
Section: Distribution and Content Of Comonomers In Polyolefinsmentioning
confidence: 99%
“…Polymer fractions are eluted by raising flow rate and temperature of the column to achieve further separation and detection. The properties of the eluate are measured by a detector or array of detectors, such as DRI, IR, ,, ELSD, or turbidity, to provide a measure of concentration as a function of temperature. The use of multiple detectors provides additional information.…”
Section: Distribution and Content Of Comonomers In Polyolefinsmentioning
confidence: 99%
“…The TGIC peak of the samples elutes in decreasing order of comonomer content, as observed in previous works. [24,27,[55][56][57][58] The elution temperature of 11 samples, issue from homogeneous catalyst [1,2] and supported catalyst [3], were plotted (Figure 2b). The peaks are rather narrow and have a similar distribution to a Gaussian which confirms that all polymers were quite homogeneous in composition.…”
Section: Chemical Composition Distributionmentioning
confidence: 99%
“…However, these techniques cannot be used for the separation of amorphous fractions of the polymers. The combination of high temperature liquid chromatography with a Hypercarb column operating with a temperature gradient [22][23][24][25][26][27] was introduced by Cong and Macko and allow the analysis of amorphous polymers. These high temperature fractionation techniques were able to determine the chemical composition distribution (CCD) of LLDPE.…”
Section: Introduction -2 -mentioning
confidence: 99%
“…[34][35][36][37] Recently, this simulation technique was applied to study polymer adsorption and shown to be very useful in the case of LLDPE adsorption onto graphene. 38 Current findings suggest that it can also be used for studying interaction forces between colloidal particles. From these information we were able to propose in this paper a scenario explaining vesicles formation in emulsion PISA.…”
Section: Introductionmentioning
confidence: 99%